2020
DOI: 10.1021/acs.inorgchem.0c00797
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomerism as an Origin of Different Reactivities of Ir(III) PC(sp3)P Pincer Catalysts

Abstract: Two stereoisomers of pentacoordinate iridium(III) hydridochloride with triptycene-based PC(sp 3 )P pincer ligand (1,8bis(diisopropylphosphino)triptycene), 1 and 2, differ by the orientation of hydride ligand relative to the bridgehead ring of triptycene. According to DFT/B3PW91/def2-TZVP calculations performed, an equatorial Cl ligand can relatively easily change its position in 1, whereas that is not the case in 2. Both complexes 1 and 2 readily bind the sixth ligand to protect the empty coordination site. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Catalysis . Initial alkene isomerization studies were conducted using five complexes reported by us in the past as catalysts for the transfer dehydrogenation of alkanes [17a,b] . Compounds 1 – 4 possess hemilabile coordinating alkoxyl groups: 1 – 3 are characterized by mer‐ configuration of the PC( sp 3 )ligand and a rigid coordination of the sidearm having a different steric bulk complex, whereas 4 is a more flexible analogue with fac ‐coordination of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysis . Initial alkene isomerization studies were conducted using five complexes reported by us in the past as catalysts for the transfer dehydrogenation of alkanes [17a,b] . Compounds 1 – 4 possess hemilabile coordinating alkoxyl groups: 1 – 3 are characterized by mer‐ configuration of the PC( sp 3 )ligand and a rigid coordination of the sidearm having a different steric bulk complex, whereas 4 is a more flexible analogue with fac ‐coordination of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Triptycenes as structures for catalysts or reagents in organic transformations have not been explored intensively. Some work highlights the use of triptycenes as a ligand/catalyst incorporating metals, mostly pincer‐type ligands/complexes in organic transformations such as alkenes [3] and 2‐methyl‐3‐butenenitrile isomerization, [4] chemoselective transfer‐hydrogenation of α,β‐unsaturated ketones, [5] transfer dehydrogenations of alkanes, [6] bis‐hydroformylation of butadiene, [7] selective hydrocyanation of butadiene, [8] cyanation of aryl bromides, [9] and cross‐coupling reactions of aryl chlorides with phenylboronic acid [10] . Very recently, triptycenyl methyl sulfide has been explored for electrophilic aromatic halogenations with N ‐halosuccinimides through the formation of sulfonium salt 1 as the active species (Figure 1a) [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Since their initial discovery by Shaw in 1976 pincer complexes have held a privileged position in organometallic chemistry. [1][2][3] Pincer complexes are widely applied in catalysis for example in iron catalysed hydrogenations, [4][5][6][7][8][9][10][11][12][13] iridium and ruthenium catalysed alkane dehydrogenation, [14][15][16][17][18][19][20][21][22][23][24][25][26][27] and cross-coupling reactivity. [28][29][30][31][32][33][34][35][36][37][38] Pincer ligands also support interesting reactivity, for example acting as a two-electron sink to augment reactivity.…”
Section: Introductionmentioning
confidence: 99%